Kolaborasi antara Auditor dan Auditee dalam Proses Pelaksanaan Audit - Rizal, Izzati (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Trust is a crucial element in the audit process that impacts the quality and success of audits. This study explores the application of social penetration theory as a strategy to build trust between auditors and auditees. The theory illustrates that interpersonal relationships develop through openness and information exchange. In the audit context, increased openness facilitates more effective communication, accelerates data collection, and reduces conflicts.The findings indicate that strong trust enhances transparency and audit quality. Competent and ethical auditors gain trust more easily, while respected auditees are more cooperative. The study recommends training in interpersonal skills for auditors and regular assessments of trust relationships. Implementing this approach will strengthen the audit process and enhance organizational accountability.